Part 8: Post-combustion CO2 capture: pilot plant operation issues. Issue 2 (April 2013) - Gelowitz, Don; Supap, Teeradet; Abdulaziz, Naami; Sema, Teerawat; Idem, Raphael; Tontiwachwuthikul, Paitoon
Pilot plant operation is a necessary step that needs to be implemented prior to full-scale commercial plant design and operation, especially for a yet-to-be commercial technology such as post-combustion CO2 capture. This article, the eighth and final part of the post-combustion carbon capture technology Review Series, highlights issues that can be encountered and methods to resolve them prior to embarking on a full-scale design and operation. In particular, the article highlights the likelihood of potential flaws in the assumptions usually made in designing absorption-based CO2 capture plants. An example of this can be seen when attempting to transpose the design philosophy in natural gas processing to amine-based CO2 capture. This article also indicates optimum operating ranges suitable to obtain optimum plant performance. Equally, it shows the impact that flue gas impurities can have on solvent stability, off-gas emissions, liquid and solid wastes generated, and overall plant performance. There is an optimum plant size that is suitable for pilot plant studies. The pilot plant should be big enough that engineering data obtained can be used reliably for plant design, and small enough to allow for plant configuration changes at a reasonable cost. This article notes that a quick chemical analysis is essential in order to establish good control of the CO2 capture process. Future trends will therefore see the development of techniques for quick online analysis.